The effect of corporate governance, tax avoidance, and profitability on earnings management - Nugrahani, Tri Siwi; Purwanti, Yuni; Muhammad, Rifqi; Grediani, Evi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
Using the agency theory approach, this study examines the influence of institutional ownership, managerial ownership, tax avoidance, and profitability on earnings management. There are 315 companies in the research sample using the purposive sampling method with the following criteria: companies listed on the IDX during the 2018-2022 period, companies that prepare annual financial statements, and non-cyclical consumer sector companies. This study used multiple linear regression analysis and a t-test with a significance level of 5% for hypothesis testing. The results show that institutional ownership, managerial ownership, and tax avoidance negatively affect earnings management, while profitability has a positive effect earnings management. These results prove that institutional and managerial ownership, and good corporate governance can reduce earnings management and tax avoidance. However, profitability also improves earnings management.